From cultural showcases to public diplomacy agents: Basque-American festivals in the United States. Issue 2 (3rd July 2019) - Goirizelaia, Maialen; Iturregui, Leire
ABSTRACT: Basque festivals in the United States have a long history. Among the festivals organized, there are festivals with different objectives. The objective of the first festivals was to unite the Basque community in the United States, as some Basques were from the Spanish side of the Basque Country and others from the French side, the objective was to unite all of them as Basques to a one-time two day festival to celebrate together and meet each other. The Western Basque Festival organized in 1959 in Sparks is an example of this. Annual Basque National Festival in Elko also wanted to have an internal joint celebration: still not focused on inviting non-Basques, but yes promoting positive image to Elko Basques. Inter-community Basque festivals have a history of over 100 years with Basques in New York in the early 1900s and western Basques since the 1920s. After that, ones Basques were united and almost settled in the United States, they started organizing festivals with another objective: invite the non Basque public and be accepted in the American society. The Boise Jaialdi Festival and Smithsonian Folklife Festival break the mould by specifically inviting the non-Basque public. What we would like to show with this research is how Basques and Basque American festivals, thanks to Public Relation activities as the festivals organized in the United States, have become public diplomacy agents and help in the relations between the United States and the Basque Country.